Conduction system pacing compared with biventricular pacing for cardiac resynchronization therapy in patients with heart failure and mildly reduced left ventricular ejection fraction: Results from International Collaborative LBBAP Study (I-CLAS) Group - Vijayaraman, Pugazhendhi; Zanon, Francesco; Ponnusamy, Shunmuga Sundaram; Herweg, Bengt; Sharma, Parikshit; Molina-Lerma, Manuel; Jastrzębski, Marek; Whinnett, Zachary; Vernooy, Kevin; Pathak, Rajeev K; Tung, Roderick; Upadhyay, Gaurav; et al. (Heart rhythm, 2025)
BACKGROUND: Cardiac resynchronization therapy (CRT) is a guideline-recommended therapy in patients with heart failure with mildly reduced ejection fraction (HFmrEF, 36%-50%) and left bundle branch block or indication for ventricular pacing. Conduction system pacing (CSP) using left bundle branch area pacing or His bundle pacing has been shown to be a safe and physiologic alternative to biventricular pacing (BVP). OBJECTIVE: The aim of this study was to compare the clinical outcomes between BVP and CSP for patients with HFmrEF undergoing CRT. METHODS: Consecutive patients who underwent BVP or CSP with HFmrEF between January 2018 and June 2023 at 16 international centers were included. The primary outcome was the composite end point of time to death or heart failure hospitalization (HFH). Secondary end points included change in left ventricular ejection fraction (LVEF) and individual end points of death and HFH. RESULTS: A total of 1004 patients met inclusion criteria: BVP, 178; CSP, 826 (His bundle pacing, 154; left bundle branch area pacing, 672). Mean age was 73 ± 13 years; female, 34%; and LVEF, 42% ± 5%. Paced QRS duration in CSP was significantly narrower compared with BVP (129 ± 21 ms vs 144 ± 19 ms; P < .001). LVEF improved during follow-up in both groups (49% ± 10% vs 48% ± 10%; P = .32). CSP was independently associated with significant reduction in the primary end point of time to death or HFH compared with BVP (22% vs 34%; hazard ratio, 0.64; 95% confidence interval, 0.43-0.94; P = .025). CONCLUSION: CSP was associated with improved clinical outcomes compared with BVP in this large cohort of patients with HFmrEF undergoing CRT. Randomized controlled trials comparing CSP with BVP will be necessary to confirm these results.
Keywords: tepový objem; Humans; srdeční resynchronizační terapie; Case-Control Studies; Heart Failure; Stroke Volume; srdeční selhání; funkce levé komory srdeční; Heart Conduction System; studie případů a kontrol; Biventricular pacing; Conduction system pacing; Female; Aged; Heart failure hospitalization; Left bundle branch area pacing; His bundle pacing; výsledek terapie; senioři; lidé; převodní systém srdeční; Cardiac Resynchronization Therapy; Mortality; Follow-Up Studies; ženské pohlaví; HFmrEF; Male; Cardiac resynchronization therapy; Retrospective Studies; Treatment Outcome; blokáda Tawarova raménka; Bundle of His; retrospektivní studie; Bundle-Branch Block; mužské pohlaví; následné studie; Hisův svazek; Ventricular Function, Left